Minerals and allied natural resources and their sustainable development : principles, perspectives with emphasis on the Indian scenario - Deb, Mihir; Sarkar, Sanjib Chandra (Springer geology., 2017)
Nonrenewable natural resources - metallic and non-metallic minerals, industrial rocks and energy resources (both organic and inorganic), have been treated in a holistic manner in this book, including two important resources (soil and water), not commonly covered in most books on this topic. For the uninitiated reader, an introductory chapter looks into some basic definitions as well as nature and characteristics of mineral deposits followed by a chapter on the different crustal processes that produce the various ore deposits in the endogenous and exogenous environments. The strength of the book lies in its critical treatment of the genetic processes of the mineral deposits, their classification and the geodynamic context of metallogeny, and coverage of sustainable development of mineral deposits with special reference to various socio-economic as well as regulatory and environmental issues that face the Indian mining industry today. The text is punctuated with examples of Indian deposits, balanced with classical deposits around the world, to cater to the interests of Indian students and the international readership. This is a book for advanced undergraduate and post-graduate students of Geology, Environmental Sciences and Natural Resource Management.